2009
DOI: 10.1161/strokeaha.108.533075
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes: Vascular or Neurodegenerative

Abstract: T ype 2 diabetes and cognitive impairment are 2 of the most common chronic conditions found in persons 60 years and older. After that age, approximately 18% to 20% of older persons have diabetes, 1 approximately 19% suffer from mild cognitive impairment in multiple domains, 2 and approximately 6% of community-dwelling individuals have some dementia. 3 The prevalence of mild cognitive impairment and dementia increases with age as does the prevalence of diabetes; there is also an alarming trend toward a younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Because Aβ 1–42 monomers and insulin compete for breakdown by insulin-degrading enzyme, which shows a stronger affinity for insulin than Aβ 1–42 monomers [72], chronic long-term hyperinsulinemia during insulin resistance may promote Aβ aggregation by preventing the breakdown of Aβ 1–42 monomers. Taken together with the present data, these studies offer further support for the suggestion that insulin and oligomeric Aβ mutually oppose, with intact insulin signaling protecting against Aβ toxicity but elevated Aβ impairing insulin signaling, consistent with the clinical finding that insulin resistance is a risk factor for AD [13, 27, 4144, 46, 47]. It is possible, and indeed likely, that the effects of chronic Aβ 1–42 elevation on brain metabolism and cognitive function may vary across time; future studies aimed at clarifying the timeline along which Aβ 1–42 oligomers impair hippocampal function by various potential mechanisms may build on the present work.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Because Aβ 1–42 monomers and insulin compete for breakdown by insulin-degrading enzyme, which shows a stronger affinity for insulin than Aβ 1–42 monomers [72], chronic long-term hyperinsulinemia during insulin resistance may promote Aβ aggregation by preventing the breakdown of Aβ 1–42 monomers. Taken together with the present data, these studies offer further support for the suggestion that insulin and oligomeric Aβ mutually oppose, with intact insulin signaling protecting against Aβ toxicity but elevated Aβ impairing insulin signaling, consistent with the clinical finding that insulin resistance is a risk factor for AD [13, 27, 4144, 46, 47]. It is possible, and indeed likely, that the effects of chronic Aβ 1–42 elevation on brain metabolism and cognitive function may vary across time; future studies aimed at clarifying the timeline along which Aβ 1–42 oligomers impair hippocampal function by various potential mechanisms may build on the present work.…”
Section: Discussionsupporting
confidence: 88%
“…A further link between insulin signaling and Aβ is suggested by the comorbidity seen between AD and type 2 diabetes mellitus, a disease characterized by impaired insulin sensitivity [13, 4144]. Postmortem analysis of brain tissue from AD patients shows several features associated with insulin resistance, prompting speculation that AD might be a type of brain diabetes [45].…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the structural brain damage underlying the association is not well understood. Diabetes leads to cerebral macro- and microvascular diseases such as stroke, white matter lesions (WMLs), and cerebral microbleeds (CMBs).…”
mentioning
confidence: 99%
“…Diabetes is associated with both vascular disease (i.e., infarcts) and neurodegenerative changes (i.e., hippocampal atrophy), which are frequently seen in Alzheimer's disease. These data suggest that, compared with nondiabetic patients, those with diabetes have brain structural changes that reflect neuronal degeneration as well as vascular damage [23].…”
Section: Editorialmentioning
confidence: 79%
“…Compared with community-dwelling, normoglycemic individuals, those with diabetes have a higher prevalence of global cognitive impairment and a higher incidence of cognitive decline. Population-based studies have also shown that diabetes is a risk factor for Alzheimer's disease [23]. An increasing body of data supports the hypothesis that diabetic pathologies lead to both Alzheimer-type neurodegeneration and vascular brain pathology, and it is this mix of these diseases that forms the anatomical basis for clinical and subclinical cognitive impairment in diabetes.…”
Section: Editorialmentioning
confidence: 95%